Mother’s Behaviour in Overcoming Noctural Enuresis in Toodlers - Dedeh Husnaniyah; Eleni Kenanga Purbasary; Gieta Ratna Sari (Journal of Nursing Care, 2021)
The developmental task that children have to go through in toddlerhood is to control bowel movements or urination. Data obtained on the incidence of enuresis in children as much as 80% is nocturnal enuresis. This requires parents to be able to educate good behavior for children regarding urination problems, especially at night. Treatments that can be done by parents to overcome bedwetting behavior in children are: firstly giving motivation to children not to wet the bed again, secondly by giving rewards if the child succeeds in not wetting the bed, the third is by behavior therapy (behavior treatment), namely exercise control urination, the fourth woke the child to urinate while sleeping at night (alarm therapy/enuresis alarm), the fifth used medical therapy/drugs, and the sixth was hypnotherapy/hypnoparenting/acupuncture. The social and psychological impacts caused by enuresis are very disturbing the lives of a child and a mother. The adverse effects of enuresis psychologically and socially will affect the quality of life of children as adults. The purpose of this study was to determine the behavior of mothers in overcoming nocturnal enuresis in toddlers in Indramayu. This research method is a quantitative research with a descriptive approach. The population in this study were mothers who had toodler children in Pabean Udik Village, Indramayu Regency. The sampling technique used total sampling technique with respondents, namely: mothers who have children aged 1-3 years as many as 92 respondents. The instrument of this study used a questionnaire made by researchers about the description of the mother's behavior in overcoming nocturnal enuresis which had been tested for validity and reliability tests. Analysis of the data used is univariate analysis in the form of presentations. The results of the research on the behavior of mothers in the poor category in overcoming bedwetting in toddlers were 52 respondents (56.5%) and the behavior of mothers with good categories in overcoming bedwetting in toddlers was 40 respondents (43.5%). The domain of maternal behavior consists of the domains of health knowledge, attitudes towards health and health practices. The behavioral domain of health practices has not been done well by mothers. This can be seen from the behavior carried out by mothers, mothers get used to scolding children to overcome bedwetting, mothers familiarize children with using pampers to prevent bedwetting, and only some mothers give gifts when children do not wet the bed to motivate children to stop wetting. The conclusion from the study was that the mother's behavior was not good in dealing with bedwetting in children. Therefore, the follow-up needed to have cadres in the community to provide education about toilet training to mothers aged 1-3 years so that the problem of nocturnal enuresis in toodler children is resolved.